Information search, integration, and personalization : 13th International Workshop, ISIP 2019, Heraklion, Greece, May 9-10, 2019, revised selected papers /: 13th International Workshop, ISIP 2019, Heraklion, Greece, May 9-10, 2019, revised selected papers. ([2020]) - Unknown
No abstract available